THE STUDY OF CONTRIBUTION OF RAJARSHI CHHATRAPATI SHAHUJI MAHARAJ IN WOMEN EDUCATION (International Journal of Food and Nutritional Sciences, 2022)
Rajarshi Chhatrapati Shahu Maharaj, a great king of his own kind is considered to be more of asocial reformer than a king. Shahu Maharaj was crowned as a King of Kolhapur State, Rajarshi ShahuMaharaj was one of the most prominent revolutionary reformers of Maharashtra. He was considered abenevolent king because he was in favor of the cause of social reform. Maharashtrian society is an eco-politicalcultural system based on certain ideologies, which is patriarchal in nature and whose mission is toimpose a male hierarchy in almost all spheres of life and women are marginalized, excluded and dominated.He sought the best solution to the question of what education is; it could empower women. For this heestablished girls' colleges and hostels and gave scholarships to girls. He also tried to implement socialchanges that would introduce laws. He wanted to bring equality between men and women. It can give women arespected status and enable them to live with dignity, honor and sociality. He did not stop his efforts towardsthe state of Kolhapur but extended it to the whole of Maharashtra (Niraj Varma and Akhilesh).Rajarshi Shahu Maharaj laid the foundation for women's education by introducing free andcompulsory primary education for women. Not stopping at this, Shahu Maharaj sent women to Mumbai andPune for education in order to get quality education. He was also tried to get education for all women of anyreligion and castes. Along with women's education, laws related to widows and women oppression were made.His contribution was not only to women education but also in the empowerment of women. Thus, it isimportant froma historical perspective and social significance.